Performance Evaluation of BioPerl, Biojava, BioPython, BioRuby and BioSmalltalk for Executing Bioinformatics Tasks - Moitra, Dipanjan; Samanta, RK (International Journal of Computer Sciences and Engineering, 2015)
In the recent years, Bioinformatics and computational biology are two of some important and active research disciplines. Finding insights into biology, information technology tools in the form of programming languages suitable for biology along with data mining tools and techniques are deployed. The open source programming languages used in bioinformatics are informally called Bio* projects. This work explores the performances of BioPerl, Biojava, BioPython, BioRuby, BioSmalltalk under Bio* projects for executing bioinformatics tasks.